Resident Doctor Duty Shift Scheduling in Tarragona, Spain - (:unkn) unknown (My University, 2022)
The goal of this thesis is to create a computer algorithm to schedule family care resident doctors’ duty shifts in Tarragona, Spain. The algorithm considers European Working Time Directive regulations which limit the number of hours any worker can work in a year. Furthermore, each health center has different work time and staffing requirements, and the medical training program requirements change based on a resident’s level of experience also known as rank of residency. Fair scheduling is essential to healthcare workers’ rights to have time to recover between shifts while satisfying all the training requirements and regulations. Integer programming is used to generate the annual duty shift schedules for more than 70 resident doctors. Two experiments–the first using real-world data provided by the resident doctor head in Tarragona and the second using fictional data–are conducted. The computer algorithm generates not only feasible but also optimal and outstanding results in most cases.